Factors influencing sexual and reproductive health perceptions among mountainous adolescents in Vietnam - Thi Hoa Huyen Nguyen; Linh Vu Manh; An Nguyen Thi; Hao Mai Thi Thuy; Linh Khanh Bui; Anh Hoang Phuong; Thuan Pham Thi; Tran Quang Duc; Huong Nguyen Thi Thanh (International Journal of Adolescence and Youth)
This cross-sectional study aimed to assess the knowledge and perceptions of sexual and reproductive health (SRH) and factors influencing perceptions among adolescents living in Son La, a mountainous region in Vietnam. A total of 382 adolescents participated in the study, with 59.7% girls and 40.3% boys. Findings revealed that the level of knowledge of SRH among adolescents in Son La is markedly different among girls and boys, where girls exhibited higher knowledge compared to boys in all aspects surveyed. The average SRH perception score was moderate (21.7 ± 8.05; maximum score = 33). Adolescents’ understanding of sexual intercourse, misconceptions related to first-time sexual experiences, and awareness of contraceptive methods were significantly associated with SRH perception scores. These findings underscore the need for targeted health education interventions in mountainous areas, emphasizing the importance of enhancing SRH knowledge and awareness among all adolescents, with gender-specific needs. Such efforts can contribute to improved SRH outcomes among adolescents in these regions.